IMPACT OF PARENTING STYLE ON CHILD DEVELOPMENT: INVESTIGATING HOW DIFFERENT PARENTING STYLES AFFECT CHILD DEVELOPMENT OUTCOMES IN IMO STATE, NIGERIA - Charles-Ebere, Ihuoma Evan (African Journal of Social and Behavioural Sciences, 2025)
The study examined the impact of parenting styles on child development, with a particular focus on how authoritarian, authoritative, permissive, and neglectful parenting styles influence children’s social, emotional, cognitive, and behavioral outcomes. The study adopted a descriptive survey design. Two research questions and two hypotheses were used for the study. A sample of 300 parents and teachers was drawn from primary and secondary schools through stratified random sampling. A structured questionnaire titled the Parenting Style and Child Development Questionnaire (PSCDQ), was used for data collection. Data were analyzed using mean and standard deviation to answer research questions, while the t-test was employed to test hypotheses at a 0.05 level of significance. Findings revealed that authoritative parenting style promotes positive developmental outcomes in children, including higher self-esteem, better academic performance, and stronger social adjustment. Conversely, authoritarian and neglectful parenting was associated with emotional instability, lower social competence, and weaker academic outcomes. The study concluded that parenting style is a critical determinant of a child’s overall development. It is recommended that parents adopt balanced, supportive, and responsive parenting approaches to enhance optimal child growth and functioning.